Chapter Distribuzione del marine litter nelle spiagge della Sardegna: il caso di Cala dei Ponzesi e di Cala Spalmatore nell'isola dell'Asinara - Contini, Massimo (Proceedings e report, 2020)
The study aims to analyze and quantify compositions of marine litter along 2 beaches of Asinara Island-Italy during 3 surveys (winter'17, spring-summer'19). Method used was based on guidelines of UNEP, JRC and DEFISHGEAR project. Preliminary results show that 1917 items were collected at Cala dei Ponzesi, while 816 were identified in 2019 surveys. 289 items were collected in 2 2019 surveys at Cala Spalmatore. It appears that plastic is the most important category of litter and plastic fragments, lolly sticks, plastic caps/lids unidentified, string and cord (<1 cm) are the most frequent debris